The word-forming semantics peculiarities of derivatives with stem каз- - Пономаренко, Валентина Дмитрівна; Дудка, Олена Олександрівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”)
The specifics of word-building semantics of the derivatives with the каз- root has been investigated in this article. Peculiarities of semantic and derivational connections between motivating and motivated words have been stated. Dependence of word-building activity of the basic verb казати from complication of its semantic structure has been found. Features of semantic realisation of a forming word in lexical meaning of derivative one have been traced.